Kasurdi health and demographic surveillance system: A profile and way forward - Arun Kumar Yadav; T Prabhakar Teli; Sanjay K Juverkar; Rahul Kumar; Renuka Kunte; Dharamjeet Singh Faujdar (Wolters Kluwer Medknow Publications, 2022)
Kasurdi Health and Demographic Surveillance System (Kasurdi HDSS) was established at Rural Health Training Center Kasurdi on February 16, 2018. Kasurdi HDSS has been established to increase the research potential of medical colleges and develop real-time data for research purposes to study the changes in population demography, health, and health-care utilization. Kasurdi HDSS currently follows 2755 individuals living in 549 households. The system collects the data from the population through annual rounds conducted by postgraduate residents of the department of community medicine. The data are collected in the digital format with the help of android-based tablets. HDSS has collected demographic data, reproductive data, data on diseases such as tuberculosis and noncommunicable diseases, and socioeconomic data. The HDSS is in the process to upgrade its data management system to a more integrated platform, coordinated and guided by national/international standards, and data sharing policy.